المقبول: استعمالاته ودلالاته لدى أهل الحديث والحافظ ابن حجر العسقلاني - Mohd Fauzi Mohd Amin; Helmi Aris; Samer Najeh Abdullah Samarh (Universiti Sains Islam Malaysia, 2024)
The study deals with the concepts of the term “acceptable” when the scholars of Hadith in general and Hafiz Ibn Hajar in his book approximation of refinement. The scholars differed in determining the degree of modernity accepted to four opinions: First: weak speech progresses to follow up to Hassan others, and this opinion Sheikh Ahmed Shaker, Sheikh Shu’aib Arnaout, Dr. Bashar Marouf Awad, because Hafiz said that the narrator of the sixth rank Lin talk only if he retires, And the modern speech described for the weak talk as is known to each student of modern science. This is the view of Dr. Walid Al-Ani, followed by some researchers, including Dr. Khuloud Al-Hakban, Dr. Shahid Karim Falih, and his article is a summary of what Dr. Al-Waid Al-Ani wrote. They supported their opinion with evidence: Including Ibn Hibban in his Saheeh, Ibn Khuzaymah in his Saheeh, and Al-Quds in the chosen. Accepted at Ibn Hajar corresponds to Imam al-Bukhaari. Ibn Hajar improved himself to the Acceptedspeech. The third view is that it is good for others, and this is the view of Professor Muhammad ‘Issa Khalifa Al-Hussein. His argument is that many scholars, such as Al-Hafiz Ibn Hajar, have improved some of the hadeeths of the narrated narrators if they have a different path. A follow-up, and the owner of this view to consider him as a follow-up promotion to Hassan others. This is the opinion of Professor Mohammed Ragheb Rashed Al-Jaitan and his argument: that the accepted is another term for the unknown or unknown, and the majority of scholars respond to the novel of the unknown because of its lack of justice and restraint, and that the conditions of the accepted Ibn Hajar does not contribute to the removal Ibn Hajar himself has set the conditions for invoking the unknown hadith to authenticate him, not from the uniqueness of his novel or from the uniqueness of his novel if he is worthy of documentation, and that the hadith An unknown person or a person who is conceited does not call out a response or accept it unless he is aware of his condition. It is clear from the above that it is acceptable either to be anonymous to the eye if one is narrated from it, and it is not related to the documentation and the wound, or it is unknown, if two or more of them are narrated by him, and he is unaware of the documentation or the wound. The sheikhs, whether he is unique to this imam or narrated by others, or narrated by the two Sahihs in their saheehs, or the ruling of imams on the health of his hadeeth or his hadeeth.